THE 2015 CEOS DISTANCE EDUCATION COURSE ON GEOLOGICAL DISASTERS MANAGEMENT - Mouratidis, A. (Bulletin of the Geological Society of Greece, 2016)
The purpose of this paper is to present the framework, content, outcomes and the lessons learnt from the 2015 Committee on Earth Observation Satellites (CEOS) course on geological disasters management, delivered within the 2015 CEOS Distance Education Course entitled “Remote Sensing Technology for Disaster Management” - a joint effort by CEOS Agencies, in particular of the Working Group on Capacity Building & Data Democracy (WGCapD) and the Working Group on Disasters (WGDisasters).